The Influence of Human Capital on Economic Growth - Riyanto Wujarso (International Journal of Science and Society, 2021)
This research examines the effect of human capital on regional financial development in West Java Province from 2017 to 2019. This study's procedure employs a quantitative approach, and the data used is secondary data. Secondary evidence in this analysis comes from BPS data reporting. Panel regression with the GLS fixed-effect model approach was used as the research technique. The results of this study are the human capital variable, namely the level of education level. Based on the estimation results in this study, the education variable is considered the variable with the most dominant influence on economic growth. This research also provides suggestions to local governments so that there is a need for an increase in regional expenditure allocations for the education and health sectors to improve the workforce's quality so that they can have high productivity that can encourage financial growth.